2019
DOI: 10.1186/s12888-019-2021-y
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid tobacco and other substance use and symptoms of anxiety and depression among hospitalised orthopaedic trauma patients

Abstract: BackgroundNo study has examined the prevalence of tobacco, other substance use, and symptoms of anxiety and depression, and rates of comorbidities among the orthopaedic trauma population, despite the impact they have on recovery from surgery. This study aims to 1) describe the rates of symptoms and substance use; 2) compare rates of symptoms and substance use among smokers versus non-smokers; and 3) examine the relationship between symptoms and substance use with smoking status.MethodsA cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Strong associations exist between depression and anxiety and previous studies have suggested that more than 50% of patients with an anxiety disorder had depression 32 . An association between tobacco use and depression has also been shown by multiple previous studies 33‐35 and cigarette use was positively associated with depressive symptoms among young people such as college students 36 . Phenotype_B (n = 4687; 52.65%) included most patients (mean (SD) age, 68.44 (19.09) years) in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Strong associations exist between depression and anxiety and previous studies have suggested that more than 50% of patients with an anxiety disorder had depression 32 . An association between tobacco use and depression has also been shown by multiple previous studies 33‐35 and cigarette use was positively associated with depressive symptoms among young people such as college students 36 . Phenotype_B (n = 4687; 52.65%) included most patients (mean (SD) age, 68.44 (19.09) years) in our study.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, drastic physical changes, strange hospital environment and uncertainty of post-injury recovery affect patients' psychology. Anxiety and depression in orthopaedic trauma patients have been reported to range between 5-35% and 13-56%, respectively [1][2][3]. Some studies have found that emotional disorder (anxiety or depression) was associated with factors such as pain, nuclear family, female sex [4], severity of injury [5], a younger age, lack of social support and use of cannabis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking rates tend to be higher in surgical populations compared with the general population [ 31 ]. In the last 10 years, three Australian studies have reported smoking rates in orthopaedic trauma [ 26 , 27 ] and acute fracture patients [ 28 ] between 19.6% and 32.8%. Older evidence suggested smoking rates in surgical patients could be as high as 38% [ 28 ].…”
Section: Methodsmentioning
confidence: 99%